An Empirical Study of The Indirect Effects of the Perceived Accessibility and Cyber Security of Mobile Banking Applications on User Loyalty to the Applications - Jung, Wonjin (International Journal of Engineering and Technology, 2019)
As the use of smart phones and mobile devices in our daily lives continues to increase today since they were launched in the late 1990s, so do cybercrimes. Because mobile users can use their devices anytime and anywhere and almost without any constraints, mobile devices give users much greater access to the Internet, websites, and mobile applications, and the more users link to networks, the more exposed they are to cyber security issues. Such user mobile network environments have degraded the perceived security of mobile applications. Conventionally, users of mobile banking applications are exposed to potential cybercrimes and sometimes actually experience cyber security incidents. Once users recognize the potential for cybercrimes, they may hesitate or even refuse to use these applications to process their monetary transactions. Under these circumstances, users’ perceptions of cyber security issues could limit their loyalty to their mobile banking applications; that is, users could stop using these applications before they even ever form any brand loyalty to the applications. Therefore, it can be inferred that users’ loyalty to mobile banking applications is likely to depend on the applications’ perceived cyber security. Many information systems (IS) and business researchers have addressed that accessibility and security are critical IS quality attributes. In short, ease of access to mobile banking applications could directly and indirectly affect not only users’ perceptions of cyber security and usability but also their loyalty to the applications. But a comprehensive IS and business literature review finds little research on the effects of mobile banking apps’ perceived accessibility, security, or usability on user loyalty to the apps. Therefore, The aims of this study are as follows: (1) to examine the direct and indirect effects of the perceived accessibility and cyber security of mobile banking applications on user loyalty to the apps and (2) to find the causal relationships among the perceived accessibility, cyber security, and usability of mobile banking applications and user loyalty to the applications. Structural equation modeling (SEM) was used to analyze the data collected by a survey. The results of analyses show the direct and indirect effects of accessibility of mobile banking apps on the perceived cyber security and usability of the apps as well as on user loyalty to the apps. The results emphasize the importance of perceived accessibility and security in understanding the factors that affect user loyalty to mobile banking applications. The results of this study also indicate that mobile banking applications should provide users with highly accessible but secured systems that make it possible for users to process essential transaction-related information and functions quickly as well as safely.